XR training and gameplay 6DoF mobility dataset - De Kunst, Sam; Marinšek Alexander; Callebaut, Gilles; De Strycker, Lieven; Van der Perre, Liesbet (Zenodo, 2023)
User mobility in extended reality (XR) can have a major impact on millimeter-wave (mmWave) links and may require dedicated mitigation strategies to ensure reliable connections and avoid service outages. The available prior art has predominantly focused on XR applications with constrained user mobility and limited impact on mmWave channels. We have performed dedicated experiments to extend the characterisation of relevant future XR use cases featuring a high degree of user mobility. To this end, we have carried out a tailor-made measurement campaign. For a description, for analysis results, and for citing the dataset, view [coming soon] Compiled tracking data into a single dataset. We recommend using Xarray and Dask for opening the tracking and controller input data, stored in `cacerumd.h5` and `cacerumdcontroller.h5`, respectively. Dask allows for lazy loading (without occupying memory), while Xarray is handy in manipulating the multi-dimensional data. The file `cacerumd_continuous_intervals.csv` describes the intervals on which data is continuously sampled at 250 Hz. The supplied photo, `cacerumd.png` shows a user conducting the T-pose in the measurement environment.